(untitled) (Revista Educação, Artes e Inclusão, 2022)
This research aimed to comprehend how the courses in the health area of a Community university in the interior of Rio Grande do Sul have been building and incorporating into the training of students the discussion on attitudinal accessibility. In this regard, seven semi-structured interviews were carried out about the theme with coordinators of the health area of the Community University. The interviews, recorded and transcribed with the consent of the participants, were examined from the Thematic Content Analysis. Of this analysis, three categories resulted from it: 1) Conceptions on inclusion and attitudinal accessibility in higher education; 2) The strategies of the courses in the construction of attitudinal accessibility; and 3) Challenges and perspectives in building a culture of accessibility within the university. From this study, the coordinators had the opportunity to rethink some practices and/or incorporate strategies that they had not previously thought about.